2012
DOI: 10.5209/rev_sjop.2012.v15.n1.37286
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Teachers' Conceptions of Assessment: A Cross-Cultural Comparison

Abstract: This paper examines the responses of two samples of prospective teachers (New Zealand, n = 324; and Spain, n = 672) to the Teachers' Conceptions of Assessment inventory (English and Spanish respectively). The inventory captures four major intentions for assessment (i.e., improvement, irrelevance, school and student accountability). The conceptions of prospective teachers about the nature and purpose of assessment are relevant, given that (a) much educational assessment is carried out in classrooms; and (b) pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
58
2
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 29 publications
1
58
2
5
Order By: Relevance
“…Even though there is strong evidence about the importance of classroom assessment, studies have reported that teacher candidate preparation has been less than adequate and that preservice assessment teaching (when it occurs) can also be diluted through teaching practice experiences and/or particular personal characteristics of the teacher candidates themselves (Campbell, 2013). Furthermore, when they begin teacher education, teacher candidates generally demonstrate negative emotions about assessment (Crossman, 2007;Smith et al, 2014) have conceptions of assessment that are from those of practicing teachers (Brown and Remesal, 2012;Chen and Brown, 2013) and while they might value the ideals of formative assessment they do not know how to implement it (Winterbottom et al, 2008).…”
Section: Previous Studies Regarding Teacher Preparation For Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Even though there is strong evidence about the importance of classroom assessment, studies have reported that teacher candidate preparation has been less than adequate and that preservice assessment teaching (when it occurs) can also be diluted through teaching practice experiences and/or particular personal characteristics of the teacher candidates themselves (Campbell, 2013). Furthermore, when they begin teacher education, teacher candidates generally demonstrate negative emotions about assessment (Crossman, 2007;Smith et al, 2014) have conceptions of assessment that are from those of practicing teachers (Brown and Remesal, 2012;Chen and Brown, 2013) and while they might value the ideals of formative assessment they do not know how to implement it (Winterbottom et al, 2008).…”
Section: Previous Studies Regarding Teacher Preparation For Assessmentmentioning
confidence: 99%
“…In a review of this literature (Hill and Eyers, 2016) four main influences were found: the teacher candidate conceptions that underpin such learning (for example, Brown, 2011;Brown and Remesal, 2012); the relationship between preservice assessment teaching and teacher candidate learning (for example, Buck et al, 2010;Siegel and Wissehr, 2011;DeLuca et al, 2012); the practical use by teacher candidates of assessment in classrooms during preparation (Graham, 2005;DeLuca and Klinger, 2010;Nolen et al, 2011; and others); and other factors such as personal dimensions (Eyers, 2014;Jiang, 2015), layered contexts (Nolen et al, 2011;Jiang, 2015) and broader policy and societal issues (Smith et al, 2014). Few, however, appear to have investigated how these aspects influence teacher candidates' assessment learning in relation to beliefs and formative practices that encourage student self-regulation.…”
Section: Previous Studies Regarding Teacher Preparation For Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…There were several studies conducted to develop a scale of teacher beliefs, such as Brown and colleagues (Brown, Hui, Yu, & Kennedy, 2011;Brown & Remesal, 2012), who developed a scale of teacher beliefs about assessment. In addition, Barkatsas and Malone (2005) developed a scale of beliefs about nature, teaching and learning mathematics for secondary school teachers.…”
Section: Introductionmentioning
confidence: 99%